DESENVOLVIMENTO E AVALIAÇÃO DO PERFIL DE SEGURANÇA E ATIVIDADE ANTITUMORAL EM CÉLULAS DERIVADAS DE LEUCEMIA MIELOIDE CRÔNICA DE NANOEMULSÕES CONTENDO EXTRATO HIDROALCOÓLICO DE AÇAÍ - Godoi, Samantha Nunes de (2022)
Cancer is one of the most prevalent pathologies worldwide, among the subdivisions of cancers are hematological, to which chronic myeloid leukemia (CML) belongs, characterized by a chromosomal translocation that generates different pathological conditions for the patient. CML has a well-established treatment, however, there are some issues such as intolerance/resistance and side effects to the treatment to be taken into account that can interfere with the patient's response to therapy, in this way, the search for innovative alternative treatments has been target of many researchers. The fruit Euterpe oleracea Mart. (açaí) is a Brazilian plant that has gained visibility in the face of several studies, this highlight is due to multiple researches in different areas of knowledge, such as anticancer. When the focus is on products of natural origin, such as açaí, a wide range of constituents compose a complex chemical matrix, providing subsidies for the most distinct applications, such as cancer. As well, reflecting on some weaknesses (photosensitivity, oxidation, degradation, among others) making it a challenge to standardize stable and effective pharmaceutical vehicles; thus it is inferred that the association of natural compounds to nanoscale systems would be a promising alternative. Therefore, aiming at an alternative treatment to CML, the objective of this study was to develop a nanosystem containing the hydroalcoholic extract of açaí obtained from in natura fruits and characterize the nanosystems in different aspects, such as: physicochemical characterization and stability evaluation in different storage conditions, evaluation of antioxidant capacity against ABTS and DPPH radicals, chemical matrix analysis, thermal analysis, evaluation of safety profile and in vitro efficacy against HFF-1 and K562 strains, respectively. Initially, the analysis of the chemical matrix of the açaí extract was carried out, demonstrating a rich composition of phenolic acids, flavonoids and anthocyanins. After evaluation against two nanosystems (liposomes and nanoemulsions), six formulations containing different concentrations of açaí extract (0.83 to 20 mg/mL) were standardized, which presented adequate nanometric characteristics: mean diameter between 172 nm and 202 nm, index polydispersity of less than 0.3, negative zeta potential (-10 to -23 mV), acidic pH and uniform morphology with spherical droplets. In addition, it was possible to highlight that the best condition for storage of formulations containing açaí extract and also the extract in its free form was under refrigeration. Regarding the antioxidant capacity, both the nanoemulsion and the free extract that showed antioxidant activity at the three different temperatures during the 30 days of evaluation, was the concentration of 4 mg/mL. Therefore, this concentration was maintained in the other evaluations. We proceeded with the thermal analysis, where a similar thermal profile was observed for the free and nanoemulsified extract. Finally, the in vitro safety profile evaluation (in healthy human fibroblast cells) demonstrated safe exposure concentrations and the non-occurrence of corona effect against RPMI and DMEM culture mediums. Meanwhile, the trials aimed at evaluating efficacy (in leukemic cells) demonstrated the efficacy of the nanoemulsion against the K562 strain in 24 hours of exposure. We highlight this study as a pioneer in the development of nanosystems containing hydroalcoholic extract of Euterpe oleracea Mart., as well as the free extract as possible alternatives in the treatment of chronic myeloid leukemia.